(untitled) (Journal of Comparative & International Higher Education, 2022)
This study describes international doctoral students’ experiences and examines the relationships between their academic goals and psychological well-being and their sense of belonging and mental toughness. We used a multiple case study design based on three international doctoral students enrolled in education programs in the United States. Findings from six interviews about their experiences with their faculty mentors and peers showed that their sense of belonging and mental toughness related to academic goals and psychological well-being. Their sense of belonging impacted their academic goals or psychological well-being based on communication and relationships with their mentors and support from their peers. Also, their mental toughness impacted their academic goals or psychological well-being based on cognition, behavior, and affection. This study calls for faculty mentors and students to communicate early namely at the on-set of their programs and to establish a positive relationship that caters to cultural acculturation, academic success, and sense of belonging.